FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PARTISIPASI MASYARAKAT DALAM PNPM UNIT PARIWISATA DI KOTA SURAKARTA (STUDI KASUS KELURAHAN SONDAKAN, LAWEYAN DAN MOJOSONGO) - Ratna Devi Septiandari; Kuswanto Nurhadi; Isti Andini (Universitas Sebelas Maret Surakarta, 2015)
National Program for Community Empowerment (NPCE ) Tourism Unit is a new program for poverty alleviation in the region Surakarta. Issues that arise in the village Sondakan, Laweyan and Village Mojosongo was once a thriving get a lot of government programs to poverty due to the potential tourist. Interaction between local communities and the tourists and immigrants affect the level of community participation. This study used a descriptive analysis of quantitative analysis tool is used is a Likert Scale to determine the level of community participation and analysis tools SPSS 17 is used to determine the factors that affect participation. The results showed that the force participation is given at all stages of PNPM Tourism Unit, mind and material donations given to the planning and implementation as well as participation in the form of money given in the stage of implementation and utilization. The level of community participation is quite high. Internal factors that affect the shape and the level of community participation is a factor the type of work, level of income, level of education and public knowledge factor. While external factors that affect the shape and the level of community participation is the city government, village government, LKM and facilitator. For that to the Surakarta City Government is expected to continue to provide support to the development of city infrastructure to ensure the maintenance of continuous functions of tourist infrastructure facilities and infrastructure that has been built. The role of government as a facilitator has become imperative in implementing a program, so that the government needs to increase capacity in the field of technical facilitators. Keywords: Community Empowerment, Participation, PNPM Tourism Unit in Surakarta